Acoustic Changes in Patients with Laryngopharyngeal Reflux Disease without Voice Complaints: A Cross-sectional Study - Tulasi Kota Karanth; Manoj Kumar; Supreet Nayyar; Rahul Gupta; Indrajeet Chauhan; Lekhraj Sonkar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: In Laryngopharyngeal Reflux (LPR), refluxate rich in acid, pepsin, and bile regurgitates above the upper oesophageal sphincter onto the laryngeal mucosa. However, not all patients with LPR present with subjective voice changes. This may be due to a gradual change in voice that remains unnoticed. The clinical subtlety is important for diagnosis or at least awareness for better treatment and care. Aim: To objectively determine preclinical acoustic changes in patients with LPR who have not reported any voice complaints. Materials and Methods: This cross-sectional study was conducted on adult patients visiting the Out-patient department of a Tertiary Care Teaching Institute in Northern India, from September 2022 to October 2022. Patients with LPR but without voice changes were included in the study. They underwent multidimensional voice analysis during the phonation of the vowel /a/. Mean fundamental frequency (MF0), absolute jitter, absolute shimmer, and Soft Phonation Index (SPI) were analysed for the sample and compared to the gender-specific mean values provided by the software used. Statistical significance was determined using the one-sample t-test. Results: A total of 27 participants (20 females, 7 males) completed the study. In the female group, the mean MF0 (204.30±32.49 Hz) was significantly lower, absolute jitter (92.41±87.93 μs), absolute shimmer (0.38±0.31 dB), and SPI (25.62±15.24) were significantly higher than the reference mean. In the male group, the mean MF0 (138.03 Hz), absolute jitter (104.01±84.28 μs), and absolute shimmer (0.34±0.16 dB) were not significantly different from the reference mean. However, SPI (25.09±16.95) remained significantly higher than the reference mean. Conclusion: Increased jitter, shimmer, and SPI are primary acoustic changes observed in patients with LPR. These changes appear even before patients experience any voice changes.